The investment behavior of buyout funds theory and evidence - Ljungqvist, Alexander; Richardson, Matthew 1964-; Wolfenzon, Daniel 1971- (National Bureau of Economic Research, 2008)
"This paper analyzes the determinants of buyout funds' investment decisions. In a model in which the supply of capital is "sticky" in the short run, we link the timing of funds' investment decisions, their risk-taking behavior, and the returns they subsequently earn on their buyouts to changes in the demand for private equity, conditions in the credit market, and funds' ability to influence their perceived talent in the market. Using a proprietary dataset of 207 buyout funds that invested in 2,274 buyout targets over the last two decades, we then investigate the implications of the model. Our dataset contains precisely dated cash inflows and outflows in every portfolio company, links every buyout target to an identifiable buyout fund, and is free from reporting and survivor biases. Thus, we are able to characterize every buyout fund's precise investment choices. Our empirical findings are consistent with the model. First, established funds accelerate their investment flows and earn higher returns when investment opportunities improve, competition for deal flow eases, and credit market conditions loosen. Second, the investment behavior of first-time funds is less sensitive to market conditions. Third, younger funds invest in riskier buyouts, in an effort to establish a track record. Fourth, following periods of good performance, funds become more conservative, and this effect is stronger for younger funds"--National Bureau of Economic Research web site